Analysis of green infrastructure accessibility in different european cities. - Luque Florido, Adrián; Martínez-Murillo, Juan Francisco; Hueso-González, Paloma; Pereira, Paulo; Leone, Michael; Ferreira, Carla; Ferreira, Antonio; Priess, Jörg; Palliwoda, Julia; Luque Florido, Adrián; Pereira, Paulo; Jacobs, Sander (My University, 2019)
Green infrastructures are configured as elements of great importance in cities, because provide a wide range of ecosystem services to population. At this point, the accessibility to them, becomes a factor of marked importance because influences a large number of parameters, such as: use variability, safety, quality and quantity.
Keywords: Accesibilidad; Servicios ecosistémicos; Infraestructura verde